Ø§Ù„ÙØ±ÙˆÙ‚ Ø§Ù„Ù„ØºÙˆÙŠØ© Ø§Ù„ÙØ±Ø¯ÙŠØ© ÙÙŠ Ø§Ù„ØªØ¹Ø¨ÙŠØ± Ø§Ù„Ø¹Ø±Ø¨ÙŠ Ø§Ù„ØªØØ±ÙŠØ±ÙŠ Ù„Ø·Ø§Ù„Ø¨Ø§Øª Ø§Ù„ÙØµÙ„ Ø§Ù„Ø®Ø§Ù…Ø³ Ø¨Ù…Ø¹Ù‡Ø¯ Ø¥Ø¨Ù† Ø§Ù„Ù‚ÙŠÙ… ÙŠÙˆÙƒÙŠØ§ÙƒØ±ØªØ§ - Hani Nurlaili Wijayanti (Lughatu Ad-dhat, 2021)
The objectives of this research are to know the aspects of the individual linguistic differences in the Arabic written expression while achieving their presence in the students of this class at one level from the cognitive side. The results of the research from this research are 1) organizing the ideas, the differences from this point of view are the logical organization of expression, the sequence of ideas in the organization of paragraphs, writing the long introduction before talking about the topic point, coordinating ideas in numbers and not in paragraphs, because the expression is not clear, The use of different pronouns in the speech, and not using punctuation marks to be symbols in understanding the readers and following the idea. 2) The length of the sentence and its shortness, and the differences from this point are in the formulation of the long sentence with no freedom of expression, the formulation of the sentence intended to art of speech or beauty in composition with far exaggeration, the element of rhetoric in expression using analogy and metaphor in speech, the use of both long sentences And short so that the long sentence is an explanation of the short sentence, and the repetition of words closely. 3) Syntax, where some structures are the result of translating the mother tongue into Arabic. 4) The color of the written expression, where the expression for the students of the fifth semester is a creative expression and the expression is in the form of the story. 5) Martyrdom in expression, as some students used to write their expressions from the Qur’an and Hadith and the opinions of other poets.